Surgery, Science and Industry - Schlich, T. author. aut Link
XI, 349 p.
Keywords: This book charts the history of the worldwide introduction of an operative treatment method for broken bones, osteosynthesis, by a Swiss-based association, called AO. The success of the close cooperation between the AO's surgeons, scientists and manufacturers in establishing a complicated and risky technique as a standard treatment sheds light on the mechanisms of medical innovation at the crossroads of surgery, science and industry and the nature of modern medicine in general.